San Juanito y la postura corporal en la niñez intermedia, periodo 2018 - Israel Oldemar, Moreta Velasquez (2018)
In the research entitled "SAN JUANITO AND THE BODY POSTURE IN INTERMEDIATE CHILDHOOD, in the students of the Nazarene Christian Educational Unit 2018", having as main objective the corporal posture in the place of studies and measuring the activity levels in the dance. The population consisted of 400 students, with a sample of 31 people consisting of 13 women with 41.93%, and 18 men with 58.06%, between 9 and 11 years of age, the present research has an almost probabilistic sample with a model a quasi-experimental cross-sectional and quantum-qualitative type, an 8-week intervention was carried out, performing dance exercises, the 5 basic positions of the dancer through dynamics, achieving an incentive for the students to adopt healthy habits in their study establishment, at times of 7:50 - 10: 5 a.m. on Tuesdays, from 10:05 - 11:25 a.m. and 12:20 - 13:40 p.m. on Thursdays, 9:50 - 11:00 a.m. on Fridays, accumulating 64 hours by means of instruments, it was measured at each student with the KINOVEA program, a post - test was taken by means of the test in which the results were at the beginning negative and at the end with positive results this can be added the short time of intervention number of population that are of great importance in the contribution and in the personal benefits of the students, thus improving the performance of the corporal positions and at the same time the San Juanito dance in the field of culture.